Isoniazid preventive therapy added to ART to prevent TB: an individual participant data meta-analysis - Ross, J; Badje, A; Rangaka, M; Walker, AS; Shapiro, A; Thomas, K; Anglaret, X; Eholie, S; Gabillard, D; Boulle, A; Maartens, G; Wilkinson, RJ; et al. (Elsevier, 2021)
Background: Isoniazid preventive therapy prevents active tuberculosis in people with HIV, but previous studies have found no evidence of benefit in people with HIV who had a negative tuberculin skin test, and a non-significant effect on mortality. We aimed to estimate the effect of isoniazid preventive therapy given with antiretroviral therapy (ART) for the prevention of tuberculosis and death among people with HIV across population subgroups.